Strategi Identifikasi Masyarakat Penerima Rumah Subsidi Kota Makassar - Fathurrahman Burhanuddin (LOSARI Jurnal Arsitektur, Kota dan Permukiman, 2021)
The subsidized housing provision program according to the government's target in providing livable houses for Low-Income Communities (MBR) needs to be implemented to solve the problem of housing needs in Makassar City. Implementation of housing provision based on target as recipients of subsidized assistance according to the MBR criteria and the problem of the Backlog. In addition, the low-income community will face strict banking regulations regarding the credit ratio limit of their incomes which have an inappropriate impact as a subsidized KPR recipients. The purpose of this study is to identify the criteria for low-income communities as recipients of subsidized housing and the terms of the credit ratio in terms of their income. The method used was to collect data at the research location using a sample based on several categories as recipients of subsidized houses, namely 1) unlivable housing condition, 2) backlog categories, home ownership and home occupancy, and 3) economic conditions. The results of this study will identify 3 (three) criteria for low-income communities as beneficiaries of subsidized housing, so that the program can be implemented according to the right target in reducing the problems of housing shortages and the economy of the low-income community.